SINTESIS DAN UJI TOKSISITAS SENYAWA ANALOG 3â, 4â-DIMETOKSI KALKON - Novianti, S.; Balatif, N.; Zamri, A. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Chalcones belong to important class of flavonoid compounds. They have also beenreported to have anticancer, antimicrobial, antifungal, antioxidant, and cytotoxicactivities. In this research, an analogous chalcone of (E)-3-(4-clorophenyl)-1-(3â,4â-dimetoxyphenyl) prop- 2-en-1-on was synthesized using microwave iradiation andnatrium hidroxide as catalyst. The compound showed a good yield, and then wascharacterized by UV spectroscopy, IR, 1 H-NMR, and Mass Spectroscopy. Its toxicityhas been identified using Brine Shrimp Lethality Test (BSLT) method on Artemiasalina Leach. The result showed that it had a good toxicity activity withLC 50 = 2.24 Î¼g/ mL and potential as anticancer.